Evaluation of Temperature Changes in the Pulpal Chamber of the Primary Tooth During Curing of Colored Compomers - Halenur Altan; Tuğrul Sarı; Gul Tosun; Zeynep Göztaş (Cumhuriyet University, 2018)
Purpose: To investigate the temperature changes in the primary teeth pulp chambers during the curing of different colored compomers Methods: Five extracted primary mandibular second molars were prepared with class II cavities. Gold, blue, green, berry, and tooth (control group) colored compomers were tested in two steps (aproximal and occlusal). Measurement of pulp chamber temperature changes during curing was performed with a J type thermocouple. The data including differences between the highest and initial temperature values were recorded and analyzed by two-way ANOVA and Mann-Whitney U tests Results: There were statistically significant differences temperature changes in groups (p< 0.05). Gold colored compomer showed the highest temperature increase in both proximal and occlusal surfaces. Tooth colored compomer(A2) showed the lower temperature increase. The temperature increase in aproximal cavities was found to be higher than the temperature increase in occlusal cavities. Conclusions: Colored compomer can be an alternative restorative materials in superficial class I and II cavities in primary teeth. Dark coloured compomers should be used in deep cavities.